Do simple and quick functional tests reflect a more comprehensive test or physical activity in daily life in healthy young subjects? - Joice Mara de Oliveira; Jéssica Amanda de Oliveira Quirino; Natielly Soares Correia; André Vinícius Santana; Diery Fernandes Rugila; Karina Couto Furlanetto (Universidade de São Paulo, 2022)
ABSTRACT Considering the wide use of functional tests and that faster and simpler evaluations are preferable, this study aimed to verify the association between five protocols of simple functional tests (timed up and go [TUG], four-meter gait speed [4MGS] and sit-to-stand [STS] in five-repetitions [STS5rep], 30-seconds [STS30sec] and one-minute [STS1min] protocols) and the six-minute walk test (6MWT), as well as physical activity in daily life (PADL) in healthy young subjects. In this cross-sectional study, PADL was quantified by a pedometer validated for step counting and we considered the mean of seven consecutive days during the time awake. We assessed functional capacity by the TUG, 4MGS, STS5rep, STS30sec, and STS1min tests and the 6MWT. A total of 79 subjects without lung functional impairments were included (49% male, aged 28 [23-36] years). Performance of simple functional tests correlated with the 6MWT (0.23<r <0.56; P<0.05 for all) and the TUG test showed the best association (R2= 0.34). However, simple functional tests did not correlate with PADL (0.03< r <0.13; P>0.05 for all). The less time-consuming functional tests were weakly-moderately related to the 6MWT in healthy young subjects. The TUG showed the best association and explained up to 34% of the 6MWT. However, the 6MWT cannot be replaced by none of these simple functional tests. Finally, functional capacity showed no association with physical activity in daily life assessed by the pedometers in this population.